Molecular characterization of Pakistani wheat genotypes for leaf rust resistance - Begum, Sania; Khattak, Sahir Hameed; Shahzad, Armghan; Noor, Saima; Zaheer uddin, Syed; Ajmal, Wajya; Zabih ullah; Farhatullah; Fayyaz, Muhammad; Ali, Ghulam Muhammad (Journal of Pure and Applied Agriculture, 2023)
Brown rust caused by Puccinia triticinia is an individual of the absolute negative and detrimental wheat disease. Issue of leaf rust and yield losses can easily be reduced by emerging new cultivars of wheat by following advanced approaches and techniques. Marker assisted selection (MAS) is one of the prominent ways to get the goals quickly and accurately. Information regarding the presence of leaf rust gene is almost zero in Pakistani accessions. Therefore, the present study was designed to find out the major leaf rust resistance genes in indigenous lines using DNA markers. A total of seven markers including three inter simple sequences repeats (ISSR) and four simple sequences repeats (SSR) were used for reorganization of resistant genes in 30 advance lines. Markers Xgwm314, Xgwm159, CsLV-34, UBC659, UBC-818 and UBC-873 showed the presence of resistant genes. Genetic variability was observed for leaf rust genes in the advance lines of Pakistan. Xgwm314 (Lr34) showed its presence in 26% of the used lines. Similarly, marker Xgwm159 (Lr60) was found to be present in 30% of wheat lines. CsLV34 was present in 13% of the wheat lines. ISSR markers were able to detect resistant genes in all of the studied lines. Moreover, this study was successful in identifying rust resistant lines and these results will help in designing and hybridization of new programs by breeders.